Myths and doubts of teenage women about body modifications and their implications on sexuality - Silvana Cruz da Silva; Lisie Alende Prates; Juliane Scarton; Camila Nunes Barreto; Camila Neumaier Alves; Laís Antunes Wilhelm; Lúcia Beatriz Ressel (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769210812 Aim: to know the myths and doubts of a group of teenage women in relation to body changes and their implications on sexuality. Method: descriptive field study, with a qualitative approach. The participants of the study were nine female teenagers. The data were collected in a public elementary school in a city of Rio Grande do Sul through the focal group technique, and analyzed according to the content analysis. Results: the most common female events in the group were related to menstruation, such as the premenstrual syndrome, menarche and virginity. It was considered that they are gifted with sociocultural meanings constructed in social conviviality of adolescents. Conclusion: the study enabled a better understanding of the influence of culture in the experience of sexuality, demonstrating the importance of seeking, along with teenagers, their understanding, their meanings, myths and doubts.